The (un)making of "CSA people": Member retention and the customization paradox in Community Supported Agriculture (CSA) in California. (January 2019) - Galt, Ryan E.; Bradley, Katharine; Christensen, Libby O.; Munden-Dixon, Kate
Abstract: Community Supported Agriculture (CSA) faces substantial challenges in increasingly saturated and competitive markets in which competitors highlight their localness. Retention of members is crucial for the model to provide benefits to farmers; otherwise, excessive losses of members requires considerable recruitment efforts and undercuts farmer well-being. We conducted statewide research on CSAs in California, including surveys of 409 former members, 1149 current members, and 111 CSA farmers, to examine former members' reasons for leaving. We answer three questions: How do former and current members differ in their satisfaction with CSA? Why do former members leave their CSAs? And, does share customization increase retention rates? Examining the datasets together shows what we call the CSA customization paradox : while it appears that former members' primary reasons for leaving could be addressed by offering them share customization, the farm-level data shows that offering share customization has no effect on CSAs' retention rates. The discussion offers three hypotheses to further examine the CSA customization paradox, and argues for a deeper theorization of CSA people to understand the limitations of share customization as a strategy for member retention. We conclude with specific routes that CSAs can take, individually and collectively, to retain members and cultivate CSA people. Highlights: Former CSA members say the share not meeting their needs is a top reason for leaving. However, CSA share customization has no effect on CSAs' retention rates. Together these findings are the customization paradox, to be investigated further. "CSA people" are those willing and able to subject themselves to CSA's requirements. CSA people can be cultivated, but structural processes are eroding the population.